Prospective study of complications of first trimester medical termination of pregnancy at tertiary care center - Rastogi, Radha; Tailor, Bharat (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: MTP (is common procedure done by obstetrician under certain circumstances as per MTP rules and guideline, but it has certain complication and data about complication are not fully available. The aims of this study are to analyse various complication and causes of this complication following MTP presenting at our hospital. Methods: This study was conducted in 100 patients coming to Pannadhay Rajkiya Mahila Chikitsalaya, RNT Medical college, Udaipur attending OPD (including emergency OPD) and IPD during August and September 2019 after MTP. This Study also included maternal mortality among all women participated in the study. Results: A total of 100 cases included in study attended OPD (including emergency OPD) and IPD during study period. All cases were eligible for inclusion in the study. Medical method of abortion (MMA) was the most common method of termination of pregnancy adopted by patient. Prolonged bleeding, anaemia and Incomplete abortion was the common complication related to MTP and manual vacuum aspiration was done in majority of cases to manage incomplete abortion in our hospital setting. Conclusions: The high rate of MTP related morbidity is due to induced abortion continue to be done at inappropriate places using inappropriate methods by person not eligible to do so.